Synthesis and optimization of colloidal silica nanoparticles and their functionalization with methacrylic acid - Arantes, Tatiane M.; Pinto, Alexandre H.; Leite, Edson R.; Longo, Elson [UNESP]; Camargo, Emerson R. (Elsevier B.V., 2012)
The synthesis of colloidal SiO2 nanoparticles was achieved via the base-catalyzed hydrolysis and polycondensation of tetraethyl orthosilicate (TEOS) in an alcoholic medium with the careful variation of the concentrations of water, ammonia and TEOS. In this study, we investigated the influence of experimental parameters on the average size of nanoparticles by means of a multivariate statistical analysis using a factorial design to create one model to predict particle size in function of experimental conditions. This model predicted that it is possible to synthesize silica nanoparticles with size in the range from 17 to 333 nm, according to the chosen condition for the amount of water, ammonia and TEOS. It was observed that only the molar amount of NH3, the molar amount of H2O and the effect from interaction between molar amount of TEOS and H2O were significant. Subsequently, surface modification of the colloidal silica was performed in situ using the coupling agent 3(trimethoxysilyl)propyl methacrylate (TMSPM). (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Silica nanoparticles; Factorial design; Particle size; Surface functionalization